Discourse Analysis in Intercultural Comunication - Andhio Alif Putra; Al-Ahmadan, Mujadid; Putra, Aidil Syah (Indonesian Journal Publisher, 2024)
In the aspect of discourse analysis, communication between different cultures is considered as a form of intercultural communication. Through language interaction, speakers express their culture by utilizing the use of language as a tool in their utterances. This indicates that in the speaking activity there has been a communication process using language. The exchange in intercultural communication through utterances can be categorized as discourse. Through the discourse, speakers can express ideas, feelings, and experiences in their culture. This means it indicates that discourse in intercultural communication is very related to the cultural rules, norms, and values.